PEMBELIAN IMPULSIF PELANGGAN PADA E-COMMERCE : PERAN PENGALAMAN PELANGGAN DALAM PERSONALISASI IKLAN (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
One of the advantages of using social commerce, especially Instagram, is the appearance of paid advertisements that suit consumer preferences, which is called personalization. Previous studies on the effectiveness of personalized advertising still show mixed results, both positive and negative. Based on the limitations of previous research, the focus of this research is to examine and analyze the effect of advertising personalization on advertising value which then influences impulse buying in social commerce and flow experience as moderation. This study used a survey method using 157 active Instagram users. The findings on the results of this study indicate that personalized advertising has a positive effect on advertising value and encourages impulse purchases. Then the flow experience was found to strengthen the value of advertising on impulse purchases. So the results of the study show that when users are fully engaged, happy, and excited when using social media, then receiving personalized advertisements that match their preferences will encourage impulse purchases.